2018
DOI: 10.1158/0008-5472.can-18-0056
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte-Driven Downregulation of Snail Restrains Effects of Drd2 Inhibitors on Mammary Tumor Cells

Abstract: While bone is a frequent target of breast cancer-associated metastasis, little is known about the effects of tumor-bone interactions on the efficacy of tumor-suppressing agents. Here we examined the effect of two FDA-approved dopamine modulators, fluphenazine and trifluoperazine, on mammary tumor cells, osteoclasts, osteoblasts, and osteocytes. These agents suppressed proliferation and migration of mammary tumor cells chiefly by antagonizing dopamine receptor D2 and reduced bone resorption by downregulating nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…RNA interference was conducted using siRNA specific to OPN (Cat #AM16708, Life Technologies) with a negative siRNA (Silencer Select #1, Life Technologies) as a nonspecific control using the previously described procedure. 44 Fluorescence resonance energy transfer (FRET) To evaluate the role of Src in response to conditioned media, Src activity was quantified by FRET imaging as previously described. 20 A Src-specific biosensor was labeled with cyan fluorescent protein (CFP) and yellow fluorescent protein (YFP).…”
Section: Application Of Fluid Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA interference was conducted using siRNA specific to OPN (Cat #AM16708, Life Technologies) with a negative siRNA (Silencer Select #1, Life Technologies) as a nonspecific control using the previously described procedure. 44 Fluorescence resonance energy transfer (FRET) To evaluate the role of Src in response to conditioned media, Src activity was quantified by FRET imaging as previously described. 20 A Src-specific biosensor was labeled with cyan fluorescent protein (CFP) and yellow fluorescent protein (YFP).…”
Section: Application Of Fluid Flowmentioning
confidence: 99%
“…The experimental procedures were approved by the Indiana University Animal Care and Use Committee and were in compliance with the Guiding Principles in the Care and Use of Animals endorsed by the American Physiological Society. In the mouse model of osteolysis, 43,44 48 BALB/c and 50 C57BL/6 female mice (~6 weeks old, Envigo) received intratibial injections of 4T1.2 and EO771 cells (2.5 × 10 5 cells in 20 μL PBS) in the left tibia, respectively. After two days of recovery, tibia loading was performed daily on the tumor-inoculated tibiae as previously described.…”
Section: Animal Modelmentioning
confidence: 99%
“…Recent studies investigating whether osteocytes influence breast and prostate cancer cell behavior showed that human prostate cancer cell lines (PC-3 and DU145) and human breast cancer cell lines (MDA-MB-231 and MCF-7) treated with conditioned medium obtained from murine osteocyte cell line MLO-Y4 cells were stimulated to proliferate [ 41 ]. Conditioned medium from murine osteocyte cell line MLO-A5 cells was able to increase the proliferation of murine breast cancer cell line 4 T1.2 cells [ 42 , 43 ]. Hence, osteocytes appear to have an impact on tumor growth.…”
Section: Osteocytes: Their Physiology and Possible Contributions Tmentioning
confidence: 99%
“…EdU Alexa Fluor 488 Imaging Kit; Thermo Fisher, Waltham, MA, USA) as previously described. 23 A Transwell chamber assay was conducted to detect invasive cellular motility, 24 and a wound-healing scratch assay was utilized to evaluate two-dimensional migratory behavior. 25 2.2 | Western blot analysis and protein…”
Section: Cell Culturementioning
confidence: 99%